The Construction of Female Otherness in Brooklyn (2015): A Simone de Beauvoir Analysis - Serlita Rindiani; Ahmad Juma Khatib Nur Ali (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2026)
Films not only function as a form of entertainment but also reflect social values and gender relations within society. One of the recurring issues represented in films is the positioning of women as secondary subjects under patriarchal structures. This study aims to analyze the representation of woman as the Other experienced by Eilis Lacey in Brooklyn (2015) using Simone de Beauvoir’s existentialist feminist theory. The reserach employed a qualitative descriptive method with documentation techniques. The collected data were analyzed based on Beauvoir’s concept of woman as the Other. The findings reveal four forms of women’s otherness represented in the film, namely dependency on others, social control and economic limitations, appearance-based judgment and social control and external influence. These findings indicate that Eilis's identity and life decisions are influenced by patriarchal values and external expectations that position her as a secondary subject. However, the film also portrays her gradual development toward greater autonomy, demonstrating her ability to challenge social pressures and assert her own identity. This study contributes to feminist film criticism by providing a deeper understanding of how the concept of woman as the Other is represented in cinematic narratives and by encouraging critical awareness of gender representation in contemporary films.